2020
DOI: 10.1161/strokeaha.119.027255
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Perfusion Identifies Patients With Stroke With Impaired Cardiac Function

Abstract: Background and Purpose— Low left ventricular ejection fraction (LVEF) leads to worse outcomes after stroke. We hypothesized that the arterial input function (AIF) variability on perfusion computed tomography, especially the time between scan onset and end of AIF (SO-EndAIF), would reflect reduction of cardiac output. Methods— Retrospective analysis of consecutive stroke patients, who underwent computed tomography between January 2013 and September 2018,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…We propose that echocardiographic and deep regional CBF assessment should be attached importance in the prognostic evaluation of aCSVD patients absent from heart failure. Previous study indicates that lower LVEF prolongs arterial input function and contributes to larger hypoperfusion volumes as well as poorer poststroke outcome [24]. Though the present study enrolled an aCSVD population with normal LVEF, we have revealed an independent positive linear correlation between deep regional CBF and LVEF after adjustment of conventional cerebrovascular risk factors including age, hypertension, Recent systemic review and meta-analysis confirms global CBF reduction in CSVD patients especially for those with WMH [25].…”
Section: Discussionsupporting
confidence: 45%
“…We propose that echocardiographic and deep regional CBF assessment should be attached importance in the prognostic evaluation of aCSVD patients absent from heart failure. Previous study indicates that lower LVEF prolongs arterial input function and contributes to larger hypoperfusion volumes as well as poorer poststroke outcome [24]. Though the present study enrolled an aCSVD population with normal LVEF, we have revealed an independent positive linear correlation between deep regional CBF and LVEF after adjustment of conventional cerebrovascular risk factors including age, hypertension, Recent systemic review and meta-analysis confirms global CBF reduction in CSVD patients especially for those with WMH [25].…”
Section: Discussionsupporting
confidence: 45%
“…The value of LVEF, a well-established predictor for left ventricular systolic function was positively associated with deep CBF after adjustment of conventional cerebrovascular risk factors including age, hypertension, symptomatic stroke and eGFR in CSVD patients. Low LVEF prolongs arterial input function and contributes to larger hypoperfusion volumes as well as poorer poststroke outcome (19). In addition, LVFS another index of left ventricular systolic function was positively associated with deep regional CBF.…”
Section: Discussionmentioning
confidence: 95%
“…In total, 103 patients including 64 males (62.1%, mean age 63.00 ± 11.57 year) and 39 females (37.9%, mean age 63.56 ± 12.27 year) were included into the present study. Among this study population, primary causes for admission were listed brie y as follow: "lacunar stroke" (33, 32.0%), "gait disturbance or bradykinesia" (23, 22.3%), "cognition decline" (14, 13.6%), "anxiety or depression" (14, 13.6%), mixed symptoms of above (19,18.4%). The clinical characteristics including demographic information, and laboratory biomedical factors between CSVD Burden low and CSVD Burden high groups were summarized in Table 1.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…A novel study found that multimodal brain imaging performed in acute stroke may accurately predict reduced left ventricle ejection fraction (LVEF). The arterial input function width on perfusion computed tomography has been shown to correlate with LVEF in AIS and to identify patients with a reduced LVEF and increased risk of worse clinical outcome 3 months after the event [122].…”
Section: Complex Cardiopulmonary Monitoring: Confounders Influencing mentioning
confidence: 99%